Polarity in Ciliate Models: From Cilia to Cell Architecture - Soares, Helena; Carmona, Bruno; Nolasco, Sofia; Viseu Melo, Luís (Frontiers in Cell and Developmental Biology, 2019)
Tetrahymena and Paramecia are highly differentiated unicellular organisms with elaborated cortical patterns showing a regular arrangement of hundreds to thousands of basal bodies in longitudinal rows that extend from the anterior to the posterior region of the cell. Thus both ciliates exhibit a permanent antero–posterior axis and left–right asymmetry. This cell polarity is reflected in the direction of the cytoskeletal appendages nucleated around each basal body such as the ciliary rootlets. Studies in these ciliates showed that basal bodies assemble two types of cilia, the cortical cilia and the cilia of the oral apparatus, a complex structure specialized in food capture. These two cilia types display structural differences at their tip domain. Basal bodies possessing distinct compositions creating specialized landmarks are also present. Cilia might be expected to express and transmit polarities throughout signaling pathways given their recognized role in signal transduction. This review will focus on how local polarities in basal bodies/cilia are regulated and transmitted through division in order to maintain the global polarity and shape of these cells and may locally constrain the interpretation of signals by different cilia. We also explore the use of Atomic Force Microscopy to investigate ciliates’ cortex features and their impact in cell polarity. We will also discuss ciliates as excellent biological models to study development and morphogenetic mechanisms and their relationship with cilia diversity and function in metazoans.